Global banking and international business cycles - Kollmann, Robert; Enders, Zeno; Müller, Gernot J. (European economic review, 2011)
This paper incorporates a global bank into a two-country business cycle model. The bank collects deposits from households and makes loans to entrepreneurs, in both countries. It has to finance a fraction of loans using equity. We investigate how such a bank capital requirement affects the international transmission of productivity and loan default shocks. Three findings emerge. First, the bank's capital requirement has little effect on the international transmission of productivity shocks. Second, the contribution of loan default shocks to business cycle fluctuations is negligible under normal economic conditions. Third, an exceptionally large loan loss originating in one country induces a sizeable and simultaneous decline in economic activity in both countries. This is particularly noteworthy, as the 2007-09 global financial crisis was characterized by large credit losses in the US and a simultaneous sharp output reduction in the US and the Euro Area. Our results thus suggest that global banks may have played an important role in the international transmission of the crisis.